Effect of BIO-P60 and BIO-T10 Applications on the Growth and Yield of Water Spinach Using a Hydroponic System - Sevirasari, Nindy; Saparso, Saparso; Hidayati, Wilujeng (AGRIUM: Jurnal Ilmu Pertanian, 2026)
Cultivating water spinach using a hydroponic system and applying biofertilizers is a modern, environmentally friendly agricultural solution. This research aimed to determine the effect of Bio P60 and Bio T10 applications on the growth and yield of water spinach in a hydroponic system. The research was conducted in Banyumas Regency, Central Java, from February to May 2025. A Completely Randomized Design was employed with 2 factors. The first factor is hydroponic systems: wick and NFT systems, and the second factor is biofertilizer: Bio P60, Bio T10, and without biofertilizer. Data were analyzed using Analysis of Variance and Tukey's test at α = 5%. The research results showed that the wick and NFT (Nutrient Film Technique) hydroponic systems produced no significant differences in plant height, number of leaves, leaf area, biological fresh weight, and economic fresh weight of water spinach. Seed treatment by soaking with Bio P60 and Bio T10 biofertilizers significantly increased the biological fresh weight and economic fresh weight of water spinach compared to without biofertilizer application. In this study, biological fresh weight is an important variable determining the high production of water spinach per plant, with correlation coefficient and path coefficient analysis values of r = 0.92 (p-value ≤ 0.01) and β = 0.94 (p-value ≤ 0.05), respectively. To improve water spinach production and encourage sustainable farming methods, it is advised to use Bio P60 and Bio T10 in hydroponic water spinach cultivation.